2020
DOI: 10.3892/ol.2020.11653
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis revealing genome‑wide chromosomal copy number variation in supraglottic laryngeal squamous cell carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a genetically complex tumor type and one of the leading causes of cancer-associated disability and mortality. Genetic instability, such as chromosomal instability, is associated with the tumorigenesis of LSCC. Copy number variations (CNVs) have been demonstrated to contribute to the genetic diversity of tumor pathogenesis. Comparative genomic hybridization (CGH) has emerged as a high-throughput genomic technology that facilitates the aggregation of high-resolution da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The gain of the 3q26 locus was remarkably related to the occurrence of human squamous cell carcinoma, including LUSC and HNSC. Hence, the gain of 3q26 was significantly associated with smoking ( Li et al, 2020a ). CDKN2A (9p21.3) encodes P16 protein that is a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…The gain of the 3q26 locus was remarkably related to the occurrence of human squamous cell carcinoma, including LUSC and HNSC. Hence, the gain of 3q26 was significantly associated with smoking ( Li et al, 2020a ). CDKN2A (9p21.3) encodes P16 protein that is a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Case 3 was short arm deletion on chromosome 16 and long arm duplication on part of chromosome 18, related to this study, Al-Qattan MM [14] found that a boy with continuous deletion of SLX4, DNASE1, TRAP1 and CREBBP genes at 16p13.3 had a wide thumb with radial angulation, mild intellectual impairment, mild facial deformity and hydronephrosis were found in this case, and the CMA results of case 3 were basically consistent with the description of symptoms, the literature on 18q12.3q23 was rarely repeated, and no relevant studies were found. In case 4, the short arm region of chromosome 20 was repeated at the long arm position of chromosome 9, there are few literatures on the ampli cation of 20p13p12.1, Li D [15] found that the CMA result of a laryngeal cancer patient was 20p13p12.1. Pachajoa H[16] found that a baby girl was diagnosed with right megaloureter 2 months after birth, and was diagnosed with mild mental retardation and slow cognitive rhythm at the age of 3, physical examination at the age of 17 revealed a round face, broad nose, xanthoxanoma of both lower eyelids, fold of inner canthus, long eyelid clefs, slow speech, poor coordination and thick hands, this case was partially consistent with the CMA results of Case 4.…”
Section: Commentmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) has emerged to promote the aggregation of high-resolution data of cancer-associated genomic imbalances as a highthroughput genomic technology. High-resolution genomic microarray CGH (Li et al, 2020). The rapidly growing CGH publication database already contains around 1500 tumours and is beginning to reveal genetic anomalies characteristic of certain forms of tumour or stages of tumour progression (Forozan et al,1997).…”
Section: Important Comparative Genomic Hybridization In Early Detecti...mentioning
confidence: 99%